News from IMO - Krilić, Tatjana (Transactions on Maritime Science, 2016)
This contribution presents a compilation of information on current work of selected IMO bodies in the period preceding the publication of this issue of ToMs. The outcome of IMO bodies responsible for safety and environment protection has been covered, aiming at informing readers on the decisions taken, as well as on the IMO instruments and/or their amendments that have entered into force.